2011
DOI: 10.1590/s0100-83582011000300025
|View full text |Cite
|
Sign up to set email alerts
|

Sementes como fonte alternativa de substâncias químicas com atividade alelopática

Abstract: 4RESUMO -Na literatura mundial, observa-se predominância das folhas como meio preferencial de estudos de compostos químicos promissores, embora informações sobre outras frações da planta também sejam encontradas. Essa tendência se deve ao fato de que a maioria dos estudos mostra as folhas com atividade potencialmente alelopática de intensidade superior à das demais frações. Nesta revisão, procurou-se compilar e analisar as informações disponíveis sobre a importância das sementes como fonte alternativa de compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
(27 reference statements)
1
4
0
4
Order By: Relevance
“…CE resulted in a similar detection of organic acids (prospecting) and phenol standards (cinnamic acids; CA). Because organic acids were more detected in shoots, especially in BHSM, and previous reports showed that allelochemicals are usually isolated from leaves [22], the fractions of the crude shoot extracts of U. humidicola were also subjected to CE.…”
Section: Discussionmentioning
confidence: 99%
“…CE resulted in a similar detection of organic acids (prospecting) and phenol standards (cinnamic acids; CA). Because organic acids were more detected in shoots, especially in BHSM, and previous reports showed that allelochemicals are usually isolated from leaves [22], the fractions of the crude shoot extracts of U. humidicola were also subjected to CE.…”
Section: Discussionmentioning
confidence: 99%
“…Poucos trabalhos avaliam a fitotoxicidade dos extratos de cascas . Evidências indicam que a localização dos aleloquímicos está relacionada com a facilidade de liberação desses compostos no ambiente (Souza Filho et al, 2011). A presença de cascas grossas nas espécies do cerrado auxilia na proteção contra a herbivoria e o fogo das queimadas, além disso, a presença de metabólitos secundários nesse tecido auxiliam na sua defesa (Marquis et al, 2002, Coutinho, 2002.…”
Section: Discussionunclassified
“…Os aleloquímicos são encontrados em diferentes partes da planta incluindo folhas, flores, raízes, colmos, frutos, cascas, sementes e grãos de pólen (Souza Filho et al, 2011). Esses metabólitos secundários podem ser liberados diretamente no ambiente por meio da exsudação radicular, volatilização, lixiviação ou decomposição do material vegetal (Moreno, 1989;Cipollini et al, 2012).…”
Section: Introductionunclassified
“…The majority of studies concerning the asymbiotic phase of AMF have focused on the effects of root exudates; however, there are only a few reports on the effects of seed exudates (Tsai & Phillips 1991). Souza Filho et al (2011 documented the importance of seeds as an alternative source of chemical compounds with allelopathic activity, considering that they represent positive signals for symbiosis with microorganisms in the soil.…”
Section: Introductionmentioning
confidence: 99%